Effect Of Macroeconomic Variables On Profitability Of Commercial Banks Listed In The Nairobi Securities Exchange - Simiyu, Christine Nanjala; Ngile, Lessah Nzioka (International Journal of Economics, Commerce and Management, 2015)
Based on vital contribution of the commercial banks to economic progression Kenya, this study endeavors to investigate the effect of macroeconomic variables on financial profitability of listed commercial banks in the Nairobi Securities Exchange (NSE) for years 2001 to 2012. Panel data analysis using Fixed Effects model was applied on the data to examine the effects of three major macroeconomic variables which included: Gross Domestic Product (GDP), Exchange rates, and interest rates on profitability of the listed commercial banks. The study findings indicated that real GDP growth rate had positive but insignificant effect to profitability of commercial banks as measured through Return On Assets (ROA). Further, real interest rates had a significant negative influence on profitability of listed commercial banks in Kenya. While the exchange rate had a positive significant effect on the profitability of listed commercial banks on Nairobi Securities Exchange.
Keywords: Return on Assets; Panel Data; Fixed Effects; Profitability; NSE; Kenya.